Heteroduplex Formation, Mismatch Resolution, and Genetic Sectoring During Homologous Recombination in the Hyperthermophilic Archaeon Sulfolobus Acidocaldarius - Grogan, Dennis W.; Mao, Dominic (Frontiers in Microbiology, 2012)
Hyperthermophilic archaea exhibit certain molecular-genetic features not seen in bacteria or eukaryotes, and their systems of homologous recombination (HR) remain largely unexplored in vivo. We transformed a Sulfolobus acidocaldarius pyrE mutant with short DNAs that contained multiple non-selected genetic markers within the pyrE gene. From 20 to 40% of the resulting colonies were found to contain two Pyr+ clones with distinct sets of the non-selected markers. The dual-genotype colonies could not be attributed to multiple DNAs entering the cells or conjugation between transformed and non-transformed cells. These colonies thus appear to represent genetic sectoring in which stretches of heteroduplex DNA formed during HR and segregated without complete resolution of inter-strand differences. Surprisingly, sectoring was also frequent in transformation with single-stranded DNAs. Oligonucleotides, for example, produced somewhat more sectored transformants when electroporated as single strands than as a duplex, although all forms (positive-strand, negative-strand, and duplex) produced a diversity of genotypes from the limited number of markers. The marker patterns in the recombinants indicate that S. acidocaldarius resolves individual mismatches through un-coordinated short-patch excision followed by re-filling of the resulting gap. These gene-conversion events exhibit little strand bias, and can occur in pre-formed heteroduplex. These properties suggest that this process does not play a central role in the fidelity of genome replication, but may generate 3’ single-strand tails, and thereby initiate the incorporation of duplex DNA into the recipient chromosome. Regardless of the molecular details of its mechanism, HR between the S. acidocaldarius chromosome and a multiply-marked DNA produces a strikingly high level of genetic diversity in a very short chromosomal interval, and suggests that HR in Sulfolobus has significant mutagenic potential if not controlled.